7+2s-6=6s+8-3s

Simple and best practice solution for 7+2s-6=6s+8-3s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+2s-6=6s+8-3s equation:


Simplifying
7 + 2s + -6 = 6s + 8 + -3s

Reorder the terms:
7 + -6 + 2s = 6s + 8 + -3s

Combine like terms: 7 + -6 = 1
1 + 2s = 6s + 8 + -3s

Reorder the terms:
1 + 2s = 8 + 6s + -3s

Combine like terms: 6s + -3s = 3s
1 + 2s = 8 + 3s

Solving
1 + 2s = 8 + 3s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-3s' to each side of the equation.
1 + 2s + -3s = 8 + 3s + -3s

Combine like terms: 2s + -3s = -1s
1 + -1s = 8 + 3s + -3s

Combine like terms: 3s + -3s = 0
1 + -1s = 8 + 0
1 + -1s = 8

Add '-1' to each side of the equation.
1 + -1 + -1s = 8 + -1

Combine like terms: 1 + -1 = 0
0 + -1s = 8 + -1
-1s = 8 + -1

Combine like terms: 8 + -1 = 7
-1s = 7

Divide each side by '-1'.
s = -7

Simplifying
s = -7

See similar equations:

| 9x^2-34x-8=0 | | 13t-48=2+14t | | 5-2x=-5 | | 3z+15=27 | | 16x^2-320=88x | | 4x-8=12+3x | | 4x^2-2x-9=7x+8 | | 2(4x-3)-=4+2x | | 3z+17=27 | | 8a=3a+35 | | 6y-7=-2y+13 | | x(x+2)=168 | | 4x^2+47x+78=0 | | 15=b-5 | | 3+5n=16 | | -4+3x=-4 | | .3x=140+x | | .8333v+1.5=.875v+1.666 | | 2x^2+6x+9=225 | | (-4)=2x+5 | | 15=b-9 | | -6x-4=-10 | | 4(7x+8)+2=28x+34 | | 7x-2=2x+18 | | x+(x+1)+(x+2)=42 | | 5x+x+10=2*5x | | 3(3x-4)+2x=4x+16 | | 2x^2+102x+2601=5625 | | z+1.1z+2.4=-0.6(z+5) | | 10t-8=12t | | 3x-5=3x+10 | | -12=m+4 |

Equations solver categories